Choice for drug or natural reward engages largely overlapping neuronal ensembles in the infralimbic prefrontal cortex - Pfarr, Simone; Schaaf, Laura; Reinert, Janine Kristin; Paul, Elisabeth; Herrmannsdörfer, Frank; Roßmanith, Martin; Kuner, Thomas; Hansson, Anita C.; Spanagel, Rainer; Körber, Christoph; Sommer, Wolfgang H. (The journal of neuroscience, 2018)
Cue-reward associations form distinct memories that can drive appetitive behaviors and are involved in craving for both drugs and natural rewards. Distinct sets of neurons, so-called neuronal ensembles, in the infralimbic area (IL) of the medial prefrontal cortex (mPFC) play a key role in alcohol seeking. Whether this ensemble is specific for alcohol or controls reward seeking in general remains unclear. Here, we compared IL ensembles formed upon recall of drug (alcohol) or natural reward (saccharin) memories in male Wistar rats. Using an experimental framework that allows identification of two distinct reward-associated ensembles within the same animal, we found that cue-induced seeking of either alcohol or saccharin activated ensembles of similar size and organization, whereby these ensembles consist of largely overlapping neuronal populations. Thus, the IL seems to act as a general integration hub for reward seeking behavior, but also contains subsets of neurons that encode for the different rewards. - SIGNIFICANCE STATEMENT Cue-reward associations form distinct memories that can act as drivers of appetitive behaviors and are involved in craving for natural rewards as well as for drugs. Distinct sets of neurons, so-called neuronal ensembles, in the infralimbic area of the mPFC play a key role in cue-triggered reward seeking. However, it is unclear whether these ensembles act as broadly tuned controllers of approach behavior or represent the learned associations between specific cues and rewards. Using an experimental framework that allows identification of two distinct reward-associated ensembles within the same animal we find largely overlapping neuronal populations. Repeated activation by two distinct events could reflect the linking of the two memory traces within the same neuron.